Molecular identification, characterization, and structure analysis of house musk shrew (Suncus murinus) leptin - Saga, Sayaka; Sasaki, Noriyasu; Arai, Toshiro (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: House musk shrew (Suncus murinus), a small experimental animal with low body fat, may be a possible model for human lipodystrophy. Leptin is an adipocyte-derived hormone thought to have an important role in the pathophysiology of lipodystrophy. The objectives of this study were to clarify the structure and distribution of suncus leptin. Materials and methods: To determine the primary structure of suncus leptin, we cloned the suncus Lep cDNA using the rapid amplification of cDNA ends method. The obtained amino acid (aa) sequence was compared with other mammals and the protein structure prediction was performed. Results: The suncus Lep cDNA encodes 170 aa. The putative suncus leptin precursor has a predicted signal peptide of 21 aa, and the mature leptin comprises 149 aa. The mature leptin is 75%–82% homologous to that of other species. Insertion of the three aa, VPQ, not seen in other mammals was found. This VPQ insertion is thought to be due to a nucleotide insertion of nine bases by slippage-like microindels. The predicted 3D structure of suncus leptin exhibited a typical four a-helix structure, however, the VPQ region protruded compared with human leptin. Lep mRNA expression was observed only in white and brown adipose tissues. Conclusion: This study revealed the structure and distribution of suncus leptin. Because the addition of VPQ, which is not found in other mammals, was observed, suncus leptin attracts attention to its physiological action, and to the possibility of being a model of human lipodystrophy. J. Adv. Vet. Anim. Res., 6(1): 1-8, March 2019